2016
DOI: 10.1111/1758-2229.12425
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiaendosymbionts in haplodiploid and diploid scolytine beetles (Coleoptera: Curculionidae: Scolytinae)

Abstract: Haplodiploidy is a sex determination system in which fertilized diploid eggs develop into females and unfertilized haploid eggs develop into males. The evolutionary explanations for this phenomenon include the possibility that haplodiploidy can be reinforced by infection with endosymbiotic bacteria, such as Wolbachia. The subfamily Scolytinae contains species with haplodiploid and diploid sex determination systems. Thus, we studied the association with Wolbachia in 12 diploid and 11 haplodiploid scolytine beet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 53 publications
5
43
0
Order By: Relevance
“…We detected Wolbachia infection in 56 specimens (47%) from four of the six dung beetle species screened (67%). This is consistent with current estimates proposing that over 40% of worldwide insect species (Stouthamer et al, 1999), and not so different from lower infection rate estimates detected in other families and species of Coleoptera (Kawasaki et al, 2016;Kajtoch and Kotaskova, 2018;Kolasa et al, 2018). Five of the Wolbachia variants we characterized belong to the Wolbachia A-supergroup, and are genetically very similar to each other (at most 42 polymorphic sites across 1,800 bp sequenced).…”
Section: Discussionsupporting
confidence: 91%
“…We detected Wolbachia infection in 56 specimens (47%) from four of the six dung beetle species screened (67%). This is consistent with current estimates proposing that over 40% of worldwide insect species (Stouthamer et al, 1999), and not so different from lower infection rate estimates detected in other families and species of Coleoptera (Kawasaki et al, 2016;Kajtoch and Kotaskova, 2018;Kolasa et al, 2018). Five of the Wolbachia variants we characterized belong to the Wolbachia A-supergroup, and are genetically very similar to each other (at most 42 polymorphic sites across 1,800 bp sequenced).…”
Section: Discussionsupporting
confidence: 91%
“…Guided by advanced pheromone attractants or sound production in the establishment of new nests, these insects have among the most advanced mating systems in animals. Subsocial life in tunnels and caves is characterized by interactions between parents and their offspring (Kirkendall et al, 1997), where diverse microbial communities potentially play an important role (Six, 2012;Dohet et al, 2016;Kawasaki et al, 2016;Mariño et al, 2017). A range of symbiotic relationships between microbes and bark beetles has evolved since Cretaceous times, particularly the cultivation of fungi seen in at least 10 independent lineages of Scolytinae (Farrell et al, 2001;Massoumi Alamouti et al, 2009;Jordal & Cognato, 2012;Kirkendall et al, 2015;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This was also the case in Chrysomelidae, with some species infected by both strains (Kondo et al, 2011,;Jäckel et al, 2013;Kolasa et al, 2017). The most varied infections were observed in Curculionidae, with supergroup B dominating, a presence of taxa infected by both A and B supergroups, and a single species infected by F supergroup (Lachowska-Cierlik et al;, Rodriguer et al, 2010aKawasaki et al, 2016) ( Fig. 7).…”
Section: Wolbachia Diversitymentioning
confidence: 67%
“…Clark et al, 2001;Lachowska-Cierlik et al;2010, Rodriguer et al;2010a, Kondo et al;, Jäckel et al, 2013Sontowski et al;, Kawasaki et al, 2016, infection was found in up to 63% of species (Hydraenidae) ( Table 1). At lower taxonomic levels, Wolbachia was found in 25% of Diabroticite (Chrysomelidae; Clark et al, 2001), 14.3-16.7% of Bruchina (Chrysomelidae; Kondo et al, 2011), 34.8% of Scolytinae (Curculionidae, Kawasaki et al, 2016) and 16.7% of Curculioninii (Toju et al, 2013). Among 54 genera in which Wolbachia infection was examined for at least 2 species, 12 genera were completely uninfected, while 6 genera were completely infected (Table 1).…”
Section: Taxonomic Coveragementioning
confidence: 95%
See 1 more Smart Citation